Hercules: Intelligent Coupling of Dual-Mode Flash Memory and Hard Disk Drive. (14th December 2020) - Cheng, Wen; Zou, Yuqi; Zeng, Lingfang; Wang, Yang
Abstract: The write performance of multi-level cell (MLC) is several times slower than single-level cell (SLC); however, the cost per bit of MLC is much lower than SLC. Dual-mode flash (the medium can be partially switched to SLC mode by programming only 1 bit in some cells) can combine SLC and MLC to provide trading density opportunity for performance. In this paper, we present Hercules —a hybrid storage system that couples dual-mode flash memory and hard drive disk (HDD)—based on the content locality principle for high storage performance. The data are divided into two types: the reference data for read operation and the delta data for write operation. The reference data are stored in SLC and the delta data in MLC or HDD in sequential orders. Hercules organizes the metadata for the mapping of the physical locations of the reference blocks and the delta data of the original blocks, intelligently identifies hot/cold data and performs the data migration between MLC and disk for performance improvements. To validate our findings, we implemented Hercules and made evaluation to show that Hercules can effectively improve the data access speed and reduce the response time, compared with the Flashcache storage structure, and in particular, with Hercules, we can achieve 10% performance improvement over the system in absence of hot delta data caching.